Peningkatan Kesadaran Sejarah Candi Gedong Songo melalui Eduwisata Berbasis Project Based Learning di SDN Candi 03 Bandungan (International Forum of Researchers and Lecturers, 2025)
In the Candi Village community, there is still a phenomenon of a lack of awareness in understanding, exploring, and experiencing the historical values contained in Gedong Songo Temple. This condition has implications for the less than optimal use of historical sites as educational facilities and media for forming local cultural identity. Efforts to increase historical awareness are considered more effective if instilled from an early age through a contextual and applied educational approach. This study focused on students of SDN Candi 03, most of whom come from four hamlets around the area, namely Talun, Nglarangan, Ngipik, and Ndarum. The community service program designed aims to provide solutions to the partner's priority problem, namely low historical awareness among students, through the application of educational tourism and Project Based Learning (PjBL) methods. Educational tourism is positioned as a learning strategy that integrates recreational and educational aspects, allowing students to gain firsthand experience in interpreting historical sites. Meanwhile, PjBL is oriented towards project-based activities that encourage active student involvement in exploring real-world problems and producing creative products or solutions. The program is divided into three main stages: preparation, activity implementation, and monitoring and evaluation. The results of these activities are expected to increase students' knowledge, awareness, and concern for local cultural heritage, while fostering a sense of responsibility in preserving Gedong Songo Temple. Thus, educational tourism and PjBL-based education can be a relevant alternative model for fostering historical awareness among the younger generation in areas surrounding historical sites.